B-cell epitopes of canine parvovirus: distribution on the primary structure and exposure on the viral surface. - Langeveld, J P (1993)
Ten antigenic sites on canine parvovirus (CPV) were mapped with a complete set of overlapping nonapeptides of the capsid proteins VP1 and VP2: five of these sites were recognized by sera from CPV-infected dogs, three were recognized by a rabbit anti-CPV antiserum, and two were recognized by murine monoclonal anti-CPV antibodies. A region covering the first 21 amino-terminal amino acid residues of VP2 was recognized by three sera from infected dogs, one neutralizing rabbit antiserum, and one neutralizing murine monoclonal antibody. Immunoabsorption experiments with full virions indicated that at least 6 of the 10 antigenic sites are located on the surface. Of these six, three sites occur in the amino terminus of VP2. When superimposed on the three-dimensional structure of canine parvovirus (J. Tsao, M. S. Chapman, M. Agbandje, W. Keller, K. Smith, H. Wu, M. Luo, T. J. Smith, M. G. Rossmann, R. W. Compans, and C. R. Parrish, Science 251:1456-1464, 1991), the other three epitopes are located on two loops of VP2 which form the highly exposed "spike" around the threefold-symmetry axis of the virus. Thus, these regions (amino terminus and loops 1 and 3) are of interest as major target sites for induction of neutralizing antibodies.